Peran Satpol PP dalam Pelaksanaan Peraturan Daerah Nomor 15 Tahun 2014 tentang, Pengendalian, Pengawasan, Penertiban, dan Peredaran Minuman Beralkohol (Studi Di Kecamatan Wangon Kabupaten Banyumas. - Satyo, Teguh (Unnes Political Science Journal, 2017)
Alcoholic beverage is one of the many factors that can trigger negative behavior. The results of this study showed that: 1) The role of municipal police in the implementation of law No. 15 of 2014 of alcoholic beverages, as well as the dissemination of  law products or  regional regulationâs socialization, those activities have been implemented quite well, by the presence of: (1) âdalwastibâ operation, it is the restraining operation, monitoring  and controlling  by conducting patrols in the objects that are considered vital;(2) Regional Regulationâs  socialization is the socialization involving relevant departments throughout the region in Banyumas 3) law enforcement activities conducted by municipal police in accordance with the legislation that are municipal police  who has a role as a public complaint,  investigators, the apparatus who made the arrest, detention, search, foreclosure, as well as the apparatus who has right to make the delegation of the legal case to prosecutor. The obstacles that the municipal police had been experienced in the enforcement of law No. 15 of 2014 came from; (1) internal obstacles such as; lack of personnel and infrastructure that do not maximal yet in supporting the municipal policeâs activities and (2) external obstacles such as; the number of offenders who remain doing violations despite previous violations have been carried sanctions in the form of closure or other, and  also it has done a coaching.